2014
DOI: 10.2188/jea.je20130097
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Recovery 5 Years After the 2004 Niigata-Chuetsu Earthquake in Yamakoshi, Japan

Abstract: BackgroundThe 2004 Niigata-Chuetsu earthquake of Japan caused considerable damage. We assessed long-term changes in psychological distress among earthquake victims during the period 5 years after the earthquake.MethodsThe participants were people aged 18 years or older living in Yamakoshi, a community in Niigata Prefecture near the epicenter. A self-administered questionnaire survey was conducted annually for 5 consecutive years after the earthquake. Response rates were 1316/1841 (71.5%) in 2005, 667/1381 (48.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 20 publications
4
27
0
Order By: Relevance
“…Women with house‐damage certification had higher psychological distress, which seems in line with other earthquake literature . In the present study, the difference between women and men did not result from differences in observed characteristics included in the regression model.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Women with house‐damage certification had higher psychological distress, which seems in line with other earthquake literature . In the present study, the difference between women and men did not result from differences in observed characteristics included in the regression model.…”
Section: Discussionsupporting
confidence: 92%
“…The present study may highlight underreported high‐risk populations for post‐disaster psychological distress: that is, the general population, not limited to people with house damage, if they lack sources of perceived social support. The present study also suggests that support from neighbors was as important as that from family at 1 year after the disaster, which expands the findings from highly struck regions or relocated people to the general population.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations